«A semiotic general art»: Image and writing in Emilio Isgrò’s cancellature - Aznar Pérez, Mario (Escritura e Imagen, 2018)
This paper proposes a critical approach to the work of the Italian artist and poet Emilio Isgrò (Barcellona di Sicilia, 1937), who merging traditional notions of image and writing has challenged the conceptions of Art and Literature as closed and exclusionary institutions. At the same time, Isgrò’s visual work dialogues critically with the language of mass media and invites us to reflect on such controversial concepts as representation and identity. In the broad framework of experimental poetry and conceptual art, we will review some of his most relevant works and we will investigate all these aspects of his poetics by attending to the dialogue they establish with the awareness of limits and the artistic procedure of the cancellature.